2008
DOI: 10.1210/en.2007-1633
|View full text |Cite
|
Sign up to set email alerts
|

Prokineticin 1 Signaling and Gene Regulation in Early Human Pregnancy

Abstract: Prokineticin 1 (PROK1) is a recently described protein with a wide range of functions including tissue-specific angiogenesis, modulation of inflammatory responses, and regulation of hematopoiesis. The objective of this study was to investigate the role of PROK1 and prokineticin receptor 1 (PROKR1) in human endometrium during early pregnancy. PROK1 and PROKR1 expression is significantly elevated in first-trimester decidua, compared with nonpregnant endometrium. Expression of PROK1 and PROKR1 was localized in gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
152
0
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(165 citation statements)
references
References 54 publications
6
152
0
7
Order By: Relevance
“…10 The difficulty in studying implantation is that tissues are collected after an implantation event has occurred, making it hard to ascertain whether differences observed are the result of a predisposing factor or implantation itself. However, our previous findings, 10 together with the purported roles of PROK1 in intrauterine implantation, [13][14][15] led us to hypothesize that dysregulated PROKR1 expression might predispose the tubal environment to ectopic pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 The difficulty in studying implantation is that tissues are collected after an implantation event has occurred, making it hard to ascertain whether differences observed are the result of a predisposing factor or implantation itself. However, our previous findings, 10 together with the purported roles of PROK1 in intrauterine implantation, [13][14][15] led us to hypothesize that dysregulated PROKR1 expression might predispose the tubal environment to ectopic pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…PROK1 has been demonstrated to regulate the expression of genes important for implantation, such as cyclooxygenase 2 (COX2), dickkhopf-1 (DKK1), and LIF, in the human endometrium. 13 Furthermore, PROK1 was recently reported to enhance the adhesion of human trophoblast cells to extracellular matrix proteins. 15 This effect was shown to be mediated through PROK1 upregulation of LIF, suggesting that increased PROK1 activity may result in enhanced endometrial receptivity.…”
Section: Discussionmentioning
confidence: 99%
“…The group of Jabbour (Cook et al, 2010,Evans et al, 2008, Maldonado-Perez et al, 2007 has reported the localization of EG-VEGF and that of its receptors in term placenta and decidua; studied its signaling pathways, and demonstrated the effect of EG-VEGF on the expression of two inflammatory and vascular mediators, the cyclooxygenase (COX)-2 and IL-8 in thirdtrimester placentas. IL-8 is a potent neutrophil chemoattractant and angiogenic factor, promoting endothelial cell chemotaxis (Winkler, 2003), whereas COX-2 is the inducible isoform of the enzyme involved in the synthesis of prostaglandins from arachidonic acid.…”
Section: Prokineticins At Term Of the Pregnancymentioning
confidence: 99%
“…The labor onset is known to be associated with inflammatory cascades in the uteroplacental unit, and EG-VEGF has been shown to regulate the production of proinflammatory cytokines and to be involved in the inflammatory response in the placenta (Catalano et al, 2010, Denison et al, 2008, Evans et al, 2008. Therefore, antagonism of prokineticin action may provide a therapy for preterm labor caused by early inflammation and contractile pathways.…”
Section: Prematuritymentioning
confidence: 99%
“…Prokineticin-1 via PKR1 regulates expression of host implatation-related gene. (Evans, et al, 2008) Dysregulation of Prokineticin signaling in fallopian tube could affect fallopian tube smooth muscle cells contractility and embryo-tubal transport providing a potential cause for ectopic pregnancy (Shaw, et al, 2010) Prokineticin-1 and its receptor gene polymorphism and haplotype were associated with idiopathic recurrent pregnancy loss. These three gene contribute to recurent pregnancy loss in the Taiwanese Han population (Su, et al) Kallman syndrome Insufficient prokineticin signaling leads to abnormal development of the olfactory system and reproductive axis in man (Dode, et al, 2006) Mutation in prokineticin-2 and PKR2 genes underlie both Kallman sydrome and idiopathic hypogonadotropic hypogonadism (Cole, et al, 2008) Behaviour Prokineticin-2 may play a role in the pathophysiology of mood disorders in the Japanese population (Kishi, et al, 2009) Prokineticin-2 may play a role in the pathophysiology of methamphetamine dependance in the Japanese population (Kishi, et al, 2010) …”
Section: Domainmentioning
confidence: 99%